Des (dés)accords grammaticaux dans la dénomination écrite de la personne en France : un tumulte graphique entre passions tristes et passions joyeuses - Manuel Perez; Katy Barasc; Hélène Giraudo (Glad!)
Today, grammatical gender is crossed by shock waves where person denomination is caught in the conflicting uses of a grammatical police and a lot of writing practices aiming only at denouncing the language phenomenological contract, i.e. the injunction of visibilization by grammatical labels, of the subpoena to the gender difference and the appropriation of the universal-generic-neutral by the masculine.Our work notes the report published by Académie française the 1st March 2019: La féminisation des noms de métiers et de fonctions, in order to question its resistant (im)postures.The critical thinking we are opening here analyses a double hegemony: the hegemony of gender social relations or police of grammatical gender and the hegemony of the phonè on the graphè or phonocracy. Their dismissal is inseparable.Actually, masculine is instituted by grammatical police and the lack of masculine marks as single and full measure of the human nature, being this human nature seized from feminine by the supplement of significance of feminine marks: paradox of an insignified and insignificant extra-significance. Alternative practices are challenging grammatical police. They are supposed to be non-discriminating but they obey the same contract: they reply to the first injunction keeping to the agreement between the sex of the referent and grammatical gender, but they correct the paradox un-signifying masculine marks and re-signifying feminine marks in order to masculine and feminine have same value of humankind.Even if it does not avoid the aporia of a submission to the referentialist logic, the present “graphical turmoil” shows a clear willingness – to make writing less discriminating – provoking restlessly general outcries and invectives. One of the often-repeated criticisms is the un-pronounceability of the proposed spellings, criticism that remind the phonocratic support of the linguistics epistemology and the ancillary relegation of writing – relegation reinforced by the Académie française report.Stating a peculiar efficiency of writing supposes breaking the link between sounds and letters, shutting down order keepers arguments. Both dismissals cannot be separated since they tackle a same system: the androphonocracy, a seat where sad passions of a threatened bequest are nourished… waiting for others jubilations.